Formulation and Evaluation of Ointment of Valproic Acid - Singh, Sudhir; Singh, Anand; Bhandari, Anil; Sharma, Satish Kumar; Singh, Sumer; Kumar, Dinesh (Asian Journal of Pharmaceutical Research and Development, 2020)
The objective of proposed study are as to the developed low dose maintenance therapy so reduce the risk of potential side-effects and improve patient compliance. The present study is focused on the development of transdermal drug delivery system (Patches) for sustain delivery of Valproic Acid.